Legaliści i rewolucjoniści – opinia społeczna o przestrzeganiu prawa - Kurczewski, Jacek; Fuszara, Małgorzata; Orzechowski, Paweł (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
This article is part of the sixty-year-old tradition of sociological and legal research initiated by Adam Podgórecki. The presented results and conclusions concern obtaining opinions on the observance and validity of the law, as well as the attitudes adopted towards it – from absolute respect for the provisions to acceptance of their circumvention or violation. The authors’ intention was to conduct two types of analyses: a comparative analysis of the distribution of answers obtained between 1964 and 2023, as well as the content of the respondents’ extensive narratives relating to the justification of their positions. Data were collected using an online self-administered questionnaire, using a university panel and “Google Forms” made available through social networking sites. Based on the research conducted, it can be concluded that commonly accepted terms such as “legalists”, “opportunists” and “anarchists” are not always adequate to the presented attitudes towards the law and are losing their relevance.